Driver, barriers, and practices towards the adoption of a sustainable supply chain and circular economy : experiences from South Africa’s flexible packaging industry - Bogie, Jill (University of Pretoria, 2022)
Mini Dissertation (MBA)--University of Pretoria, 2021.